Assessing administrative databases for surveillance of depressive disorders in Newfoundland and Labrador - Alaghehbandan, Reza, 1971- (2010)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2010. Medicine Includes bibliographical references (leaves 91-101) The objective of this study was to assess the usefulness of provincial administrative databases in carrying out surveillance on depressive disorders. Electronic Medical Records (EMR) at three family practice clinics in St. John's were audited based on a sample of patients classified as being diagnosed or not diagnosed with a depressive disorder. The EMR served as the "gold standard", which was then compared to these same patients investigated through the use of various case definitions applied against the provincial hospital and physician administrative databases. Variables used in the development of the case definitions were depressive disorders diagnoses (either in hospital or physician claims data), date of diagnosis, and service providers type (general practitioners vs. psychiatrists). This study found that provincial hospital and physician databases are useful for carrying out surveillance on depressive disorders using certain types of case definitions. The inclusion of medications dispensed to patients was found to increase the sensitivity and decrease the false negative rate for certain case definitions. The availability of prescription data from population-based Pharmacy Networks in the development of case definitions presents an opportunity for the development of more advanced surveillance methods for depressive disorders in Canada.